KAJIAN RETORIKA CALON BUPATI DAN WAKIL BUPATI DALAM DEBAT PEMILIHAN KEPALA DAERAH KABUPATEN KAPUAS HULU 2020 - Rini Novianti; Ahmad Rabi’ul Muzammil; Agus Syahrani (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2022)
AbstractThe background of this research is to analyze and fan the contents of the debate ofcandidates for Regent and Vice Regent kapuas Hulu 2020 in terms of ethos, pathos, and logos. The purpose of this study is to find out the content of the debate of candidates for Regent and Vice Regent of Kapuas Hulu 2020 in terms of ethos, pathos, and logos. This research uses deskritive methods and the approach used isa qualitative approach. The data in this study was sourced from the content of the debate of candidates for Regent and Vice Regent of Kapuas Hulu 2020 and avideo originated on the youtobe channel entitled open debate between candidates for Regent and deputy Regent of Kapuas Hulu 2020. Based on the results of the analysis of data on the content of the debate and the video, it can be concluded that each candidate pair of regional heads uses rhetoric in the form of ethos, pathos, and logos in delivering their speech. Then this research has a link to the learning of Indonesian Language and Literature class X odd semester curriculum 2013 refers to Basic Competencies 3.12 and 4.12. The results of this study are expected to be useful, especially for teachers, learners, and for future researchers.Keywords: Debat, Ethos, Logos, Pathos, Rhetoric.